Genetic Algorithm for Combined Speaker and Speech Recognition using Deep Neural Networks - Gurpreet Kaur; Mohit Srivastava; Amod Kumar (Journal of Telecommunications and Information Technology, 2018)
Huge growth is observed in the speech and speaker recognition ﬁeld due to many artiﬁcial intelligence algorithms being applied. Speech is used to convey messages via the language being spoken, emotions, gender and speaker identity. Many real applications in healthcare are based upon speech and speaker recognition, e.g. a voice-controlled wheelchair helps control the chair. In this paper, we use a genetic algorithm (GA) for combined speaker and speech recognition, relying on optimized Mel Frequency Cepstral Coeﬃcient (MFCC) speech features, and classiﬁcation is performed using a Deep Neural Network (DNN). In the ﬁrst phase, feature extraction using MFCC is executed. Then, feature optimization is performed using GA. In the second phase training is conducted using DNN. Evaluation and validation of the proposed work model is done by setting a real environment, and eﬃciency is calculated on the basis of such parameters as accuracy, precision rate, recall rate, sensitivity, and speciﬁcity. Also, this paper presents an evaluation of such feature extraction methods as linear predictive coding coeﬃcient (LPCC), perceptual linear prediction (PLP), mel frequency cepstral coefﬁcients (MFCC) and relative spectra ﬁltering (RASTA), with all of them used for combined speaker and speech recognition systems. A comparison of diﬀerent methods based on existing techniques for both clean and noisy environments is made as well.